THE EFFECT OF TIDAL HYDRO-DYNAMICS ON THE MEASUREMENT OF RIVER FLOW VELOCITY USING CURRENTMETER - Indra Setya Putra; Budi Triadi (JURNAL TEKNIK HIDRAULIK, 2016)
River is one of the water resources is used as human needs such as irrigation and raw water supply particularly with its tidal influence. So it requires data such as velocity. Until this period standard for measuring the velocity is just arranged in non-tidal rivers with SNI 03-2414-1991. This research aims to examine methods to measure water velocity in rivers which are influenced by tidal hydrodynamics. This is also to provide recommendations for the design of new SNI for measuring the velocity of the tidal rivers. Methods which are used by conducting velocity measurements in Kapuas and Katingan rivers and by dividing the cross section into 3 sections with interval of 1 hour during 26 hours. Measurements were made using 5 points in depth (d), are 20 cm, 0,2d, 0,4d, 0,6d, 0,8d. It also carried out measurements of water level for 15 days with intervals of 1 hour. Flow velocity Distribution both horizontal and vertical are showing different patterns and having two ways of directions. The results of this study are 9 requirements for the the duration and period of current measurement in tidal rivers, 3 hydrodynamics conditions and 3 recommendations that must be noticed while measuring.